Perspektif Etika Pendidikan Menghadapi Potensi Bias Kognitif Dalam Pembelajaran Pendidikan Agama Islam - Eneng Humaeroh; Saepudin Saepudin (INTELEKTIUM, 2026)
This article aims to explore educational ethics that can be applied to address potential cognitive biases in learning, which are systematic deviations in thinking. These biases can disrupt the fairness and effectiveness of the teaching and learning process. This research analyzes concepts of cognitive biases and principles of educational ethics, as well as their implications for interactions in learning. The research findings indicate that the principles of educational ethics, such as fairness, transparency, and inclusive, can be used as strategies to mitigate the impact of cognitive biases. This article also provides practical recommendations to raise awareness of potential biases in learning